Cultural and Generational Influences on Information Privacy Concerns within Online Social Networks: An Empirical Evaluation of the Miltgen and Peyrat-Guillard Model. Issue 4 (2nd October 2017) - Arslan, Faruk; Dayyala, Niharika
ABSTRACT: Growing use of the data generated via online social networking sites (SNS) for big data analytics renders the topic of information privacy as a critical concern and calls for a deeper investigation of individuals' information privacy beliefs and behaviors. The primary goal of our research is to empirically test the effectiveness of the Miltgen and Peyrat-Guillard model in explaining the information privacy behavior of social network site users using a large-N sample from the European Union (EU). Results from the factor-based partial least squares - structural equation modeling (PLS-SEM) analysis provide partial support to this model. We elaborate on enhancements and discuss possible extensions to the model.